What makes mental health and substance use services youth friendly? A scoping review of literature - Lisa D. Hawke (BMC Health Services Research, 2019)
Abstract Background There are increasing calls to make mental health and substance use services youth friendly, with hopes of improving service uptake, engagement and satisfaction. However, youth-friendliness in this area has not been clearly defined and there is a lack of information about the characteristics that make such services youth friendly. The purpose of this scoping review was to examine the literature available on youth-friendly mental health and substance use services in order to identify the characteristics, outline the expected impacts, and establish a definition. Methods A scoping review of seven databases and grey literature sources was conducted. Twenty-eight documents were retained as relevant to the research questions. Relevant data from these documents was extracted, analyzed and presented to stakeholders, including youth, caregivers and service providers to validate and refine the results. Results Youth-friendly mental health and substance use services include integrated, inclusive, confidential and safe organization and policy characteristics; bright, comfortable, environment with informational materials; welcoming and genuine service providers with appropriate communication and counselling skills; an accessible location; minimal wait times; and individualized and innovative approaches. All areas in which youth friendliness should be implemented in a mental health and substance use service organization had a core value of youth voice. Conclusion Improving the youth friendliness of mental health and substance use services includes incorporating youth voice in organization, policy, environment, service providers, and treatment services, and has implications for treatment uptake, engagement and satisfaction. Further research is required to determine the impact of youth friendliness in such services.